Comparison between natural and accelerated carbonation (3% CO2): Impact on mineralogy, microstructure, water retention and cracking. (July 2018) - Auroy, Martin; Poyet, Stéphane; Le Bescop, Patrick; Torrenti, Jean-Michel; Charpentier, Thibault; Moskura, Mélanie; Bourbon, Xavier
Abstract: The consequences of accelerated carbonation at 3% CO2 were compared with those of natural carbonation (0.04%). Cement pastes (CEM I and CEM V/A) as well as the three major constitutive phases (C-S-H of different C/S ratios, portlandite and ettringite) were used and changes in the mineralogy, microstructure, water retention and cracking were investigated. The main conclusion was that accelerated carbonation at 3% CO2 was representative of natural carbonation although it promoted the precipitation of metastable calcium carbonate (aragonite and vaterite) in place of calcite. The results also showed that the presence of aragonite and vaterite were characteristic of the carbonation of ettringite and C-S-H respectively.